Alternative splicing modulation mediated by G-quadruplex structures in MALAT1 lncRNA - Ghosh, Arpita; Pandey, Satya Prakash; Ansari, Asgar Hussain; Sundar, Jennifer Seematti; Singh, Praveen; Khan, Yasmeen; Ekka, Mary Krishna; Chakraborty, Debojyoti; Maiti, Souvik (Nucleic Acids Research, 2022)
MALAT1, an abundant lncRNA specifically localized to nuclear speckles, regulates alternative-splicing (AS). The molecular basis of its role in AS remains poorly understood. Here, we report three conserved, thermodynamically stable, parallel RNAG-quadruplexes (rG4s) present in the 3' region of MALAT1 which regulates this function. Using rG4 domain-specific RNA-pull-down followed by mass-spectrometry, RNA-immuno-precipitation, and imaging, we demonstrate the rG4 dependent localization of Nucleolin (NCL) and Nucleophosmin (NPM) to nuclear speckles. Specific G-to-A mutations that abolish rG4 structures, result in the localization loss of both the proteins from speckles. Functionally, disruption of rG4 in MALAT1 phenocopies NCL knockdown resulting in altered pre-mRNA splicing of endogenous genes. These results reveal a central role of rG4s within the 3' region of MALAT1 orchestrating AS.